Introduction to environmental management : for the NEBOSH certificate in environmental management - Waters, Brian, 1946- (2020)
"This book is directly aligned to the NEBOSH Certificate in Environmental Management, which is a qualification aimed primarily at those in business who influence the environmental performance of their organisation by the decisions that they make as managers or the actions that they take as operators. This book aims to provide an introduction to the main areas of concern and how the challenges can be addressed. This new edition takes account of recent changes in international guidance and legislation and the recent update of the International Standard in Environmental Management ISO 14001. The contents are important for businesses that wish to stay within the law and avoid adverse publicity. It explains how the concept of sustainability can be achieved in practice and what benefits - especially financial - that can accrue. Recent developments in the definitions of sustainability and the growing interest in the circular economy are introduced. It pays to be ahead of the game because decisions made now need to reflect an awareness of the coming pressures and there are opportunities available that can bring other benefits. This book is intended for candidates for the NEBOSH qualification, but it will also be useful to anyone who wishes to understand the problems and how they can be tackled within their own organisations be they industry, public service, voluntary bodies or even as individuals"--
Revised edition of the author's Introduction to environmental management, 2013.
Includes bibliographical references and index.
Keywords: Environmental management